Analysis of the worsening nutritional quality of the Brazilian population - Passos, Luiz Marcelo (Seven Editora, 2024)
In this article, the objective is to promote a reflection on the relationship between eating habits and processed foods. Based on the reading of texts, it is intended to bring to light pertinent information about the dietary influence harmful to public health, to know the process of identification of components present in industrialized foods, thus evidencing the harms of their exaggerated intake for our health. Factors such as chronic inflammation at the cellular level, often induced by processed foods, low in nutrients and high in refined carbohydrates and trans fats, play a critical role in human health. The consumption of ultra-processed foods is responsible for approximately 57,000 premature deaths of people between 30 and 69 years of age per year in Brazil. In Brazil, in 2022, the national average showed that 31.2% of adolescents were overweight, almost double the global average (18.2%). DOI:https://doi.org/10.56238/sevened2024.001-057